2017
DOI: 10.4103/aer.aer_40_17
|View full text |Cite
|
Sign up to set email alerts
|

“Comparison of nalbuphine hydrochloride and fentanyl as an adjuvant to bupivacaine for spinal anesthesia in lower abdominal surgeries:” A randomized, double-blind study

Abstract: Background and Aims:Opioids have been favored as adjuvants to local anesthetics during spinal anesthesia. Nalbuphine, a μ-receptor antagonist and ĸ-receptor agonist, seems to be a suitable adjuvant to local anesthetics. The aim of this study was to compare postoperative analgesia and adverse effects of nalbuphine and fentanyl when used as an adjuvant to hyperbaric bupivacaine during spinal anesthesia.Materials and Methods:Sixty patients belonging to the American Society of Anesthesiologists Physical Status I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This may be attributed to the high lipid solubility leading to rapid tissue uptake of both fentanyl and nalbuphine. This complies with Prabhakaraiah et al’s (2017) study, which documented comparable sensory and motor onset between fentanyl and nalbuphine in lower abdominal surgeries, although fentanyl provided a statistically early onset of sensory than nalbuphine in Gurunath and Madhusudhana’s (2018) trial of lower abdominal surgeries and Bisht and Rashmi’s (2017) study in total abdominal hysterectomy patients. In contrast, Ahluwalia et al (2015) observed earlier onset of sensory block in the nalbuphine group than in the control group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This may be attributed to the high lipid solubility leading to rapid tissue uptake of both fentanyl and nalbuphine. This complies with Prabhakaraiah et al’s (2017) study, which documented comparable sensory and motor onset between fentanyl and nalbuphine in lower abdominal surgeries, although fentanyl provided a statistically early onset of sensory than nalbuphine in Gurunath and Madhusudhana’s (2018) trial of lower abdominal surgeries and Bisht and Rashmi’s (2017) study in total abdominal hysterectomy patients. In contrast, Ahluwalia et al (2015) observed earlier onset of sensory block in the nalbuphine group than in the control group.…”
Section: Discussionsupporting
confidence: 88%
“…Moustafa et al’s (2016) study also demonstrated prolonged duration of analgesia and a reduced visual analogue score (VAS) with nalbuphine in caesarean section patients. In contrast, Prabhakaraiah et al (2017) found higher VAS pain scores in the nalbuphine group undergoing lower abdominal surgeries. Since our study did not examine the postoperative VAS score and analgesic requirement, we can neither support nor refute these findings.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…By acting on μ1 and μ2 receptors, fentanyl is a stronger agonist than nalbuphine to produce analgesia and respiratory depression, and by acting on kappa receptors, nalbuphine may provide better effects of analgesia and sedation ( Chen et al, 1993 ). Specifically, nalbuphine acts as a moderate-efficacy partial agonist or antagonist of the µ-opioid receptor (MOR) and as a high-efficacy partial agonist of the κ-opioid receptor (KOR) ( Schmidt et al, 1985 ; Chen et al, 1993 ), which has the potential to maintain or even enhance μ-opioid-based analgesia while simultaneously mitigating the µ-opioid side effects ( Prabhakaraiah et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous study by Prabhakaraiah et al [ 8 ], the mean duration of postoperative analgesia was taken into consideration, and the duration was 180.50 ± 34.58 in group BN (nalbuphine group) and 198.67 ± 45.67 in group BF (fentanyl group) with 80% power and at a 5% level of significance. The sample size required in each group was taken as 79, and 5% dropouts were taken into consideration.…”
Section: Methodsmentioning
confidence: 99%